Editorial. Issue 1 (1st March 2014) - Wilkinson, Nicholas
Abstract : Hugh Pearman, on page 75 of the new September RIBA Journal, (In part 3 CULTURE) Pearman 2013, explains the changes he has brought about in terms of content, design and physical feel. This is to his credit to have been able to do this. The RIBA journal is now a very pleasant read, very sensitively laid out with quality colour images. Now that the editor Hugh Pearman has got this far I think it will be well maintained and carry itself through any difficult times.